2021
DOI: 10.47960/2303-8616.2021.14.13
|View full text |Cite
|
Sign up to set email alerts
|

Association of Resilience With Quality of Life and Self-Esteem in Healthcare Workers of Covid-19 Hospital

Abstract: Introduction: The coronavirus disease 2019 (COVID-19) pandemic has put national health systems under extremely large pressure. Health systems throughout the world demonstrated different levels of preparedness for COVID-19 pandemic. Aim: The aim of the study was to investigate the association of resilience with quality of life and self-esteem in healthcare workers of COVID-19 hospital. Methods: We performed a cross-sectional study between November 2020 and February 2021 in COVID-19 hospital at the University Cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 18 publications
2
1
0
Order By: Relevance
“…Self‐esteem and resilience were significantly positively correlated with each other in the current study. This result is consistent with a previous study on resilience and self‐esteem in healthcare workers of a COVID‐19 hospital in Bosnia, which concluded that resilience and self‐esteem were statistically significantly correlated with one another (Franjić et al, 2021 ). The author highlighted that resilience and self‐esteem reduced the effect of negative life events on positive social adjustments (Franjić et al, 2021 ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Self‐esteem and resilience were significantly positively correlated with each other in the current study. This result is consistent with a previous study on resilience and self‐esteem in healthcare workers of a COVID‐19 hospital in Bosnia, which concluded that resilience and self‐esteem were statistically significantly correlated with one another (Franjić et al, 2021 ). The author highlighted that resilience and self‐esteem reduced the effect of negative life events on positive social adjustments (Franjić et al, 2021 ).…”
Section: Discussionsupporting
confidence: 93%
“…This result is consistent with a previous study on resilience and self‐esteem in healthcare workers of a COVID‐19 hospital in Bosnia, which concluded that resilience and self‐esteem were statistically significantly correlated with one another (Franjić et al, 2021 ). The author highlighted that resilience and self‐esteem reduced the effect of negative life events on positive social adjustments (Franjić et al, 2021 ). A high level of self‐esteem not only helps individuals to develop themselves despite existing challenges but also protects increases resiliency (Arslan, 2016 ).…”
Section: Discussionsupporting
confidence: 93%
“…This finding suggested that increasing resilience and social support can improve the quality of life of primary glaucoma patients in clinical practice. Studies done in other chronic medical conditions showed similar trend: inflammatory bowel disease [23], recurrent coronary artery disease [24], Parkinson's disease [25], rheumatoid arthritis [26], epilepsy [27], diabetes [28] and colon cancer [29]. This study shows that in combination resilience and duration of disease significantly accounted for 13.6% of total life satisfaction of the patients although further analysis was not done to determine the other contributors to life satisfaction.…”
Section: Discussionmentioning
confidence: 52%